2014
DOI: 10.1186/1472-6955-13-19
|View full text |Cite
|
Sign up to set email alerts
|

A meaningful daily life in nursing homes - a place of shelter and a space of freedom: a participatory appreciative action reflection study

Abstract: Background: Shortcomings in elderly care have been reported in many parts of the world, including Sweden. However, national guidelines for elderly care have been introduced in Sweden, which contain core values and local guarantees of dignity. These highlight the need for dignity and well-being, and organising the older person's daily life so that they perceive it as meaningful. Therefore, the aim of the present study was to describe older persons' experience and knowledge about obstacles, opportunities and sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 40 publications
5
55
0
1
Order By: Relevance
“…This is consistent with a previous study with older persons in nursing homes, wherein they explained that they felt secure and at home due to the staff’s encounters with them and that this creates a meaningful daily life [28]. …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with a previous study with older persons in nursing homes, wherein they explained that they felt secure and at home due to the staff’s encounters with them and that this creates a meaningful daily life [28]. …”
Section: Discussionsupporting
confidence: 91%
“…This is in line with older persons’ preferences to keep their habits and routines in nursing homes to help ensure a meaningful daily life [28]. Their identity can be threatened when health deteriorates and they can no longer maintain habits and routines [33].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Along with a sense of belonging, positive relations are included in most professional understandings of the concept of well‐being . Having positive relations presume mutual love, care and considerations, all of which are regarded as principal requirements for well‐being . The present study showed the importance of being related to family, friends and the NH staff in order to experience JOL.…”
Section: Discussionmentioning
confidence: 60%
“…From a nursing geography perspective, it is not possible to separate people from places and vice versa (Andrews, 2003). This implies that people construct places and are at the same time constructed by them (James, Blomberg, & Kihlgren, 2014;Kim, 2010;Tuan, 1977). This means that the interactions and involvement of people in shared spaces is very much conditioned by the ways in which physical care environments are constructed (Andrews, 2002).…”
Section: Introductionmentioning
confidence: 99%